Program Kebun Percontohan untuk Edukasi Ketahanan Pangan di Desa Retraen, Amarasi Selatan, Kabupaten Kupang - Anjelyn Norlintya Ringa Reo; Reinald Juanli Kota; Indriyati Indriyati; Yasinta Palan Peten; Yohanes K. Ethelbert; Kristianus Simon H. Molan (Universitas Negeri Gorontalo, 2025)
Food security is a crucial issue, especially in areas with challenging geographical and climatic conditions such as Retraen Village, Amarasi Selatan Subdistrict, Kupang Regency. To address this issue, the Demonstration Garden Program was designed as an educational effort to increase community awareness and understanding of the importance of local food security. This program aims to provide practical knowledge to villagers on appropriate, sustainable crop cultivation techniques that suit the local environment. The implementation of the program consists of three main stages: preparation, implementation, and evaluation. Activities were carried out using a participatory approach to ensure community involvement in every process. The results showed an increase in community participation, improved understanding of cultivation techniques, and the emergence of local initiatives to develop gardens independently. This program is expected to serve as a learning model that can be replicated in other areas and to promote local food self-sufficiency in a sustainable manner.